Removal of Perchlorate (ClO₄⁻) from Water Using Pulsed Arc Electrohydraulic Discharge (PAED) - Deng, Dong (My University, 2010)
p.p1 {margin: 0.0px 0.0px 0.0px 0.0px; font: 11.5px Times}
Pulsed Arc Electrohydraulic Discharge (PAED) is a direct plasma water treatmenttechnology that can generate physical and chemical reactions in a single unit process to treat a broad range of chemical and biological contaminants. Karpel Vel Leitner et al. (2005) demonstrated that PAED is capable of treating contaminants via the reduction
mechanism, as they reduced nitrate to nitrite. Perchlorate is a difficult-to-treat contaminant with significant negative impacts on human health. One treatment approach for perchlorate is to reduce it. Therefore, laboratory experiments were designed and conducted to examine the efficacy of PAED for reduction of perchlorate in a water matrix.
A 3L stainless steel cylindrical reactor with two titanium electrodes connected to a 0.3 kJ/pulse pulsed arc power supply was used for the treatment processes. Three sets of factorial experiments were performed to determine: a) the power supply settings and water matrix properities for optimal ozone and hydrogen peroxide production; b) the efficacy of PAED for the reduction of perchlorate; and c) the power supply settings and water matrix properties for optimal perchlorate reduction.
The results of these experiments indicated that as much as 0.0544 mg/L of ozone was generated, with water conductivity and the presence of dissolved oxygen being the most important factors contributing to ozone generation. Hydrogen peroxide was not generated in detectable amounts under any of the conditions employed in these experiments. Finally, perchlorate was not reduced by detectable concentration in any of the conditions employed in these experiments.
Keywords: Civil Engineering; Civil Engineering